LEARNING MANAGEMENT OF ISLAMIC CLASSIC BOOKS: A CASE STUDY AT ASY SIFA ISLAMIC BOARDING SCHOOL - Muhamad Syara Nurhakim; Asep Budi (Cakrawala Pedagogik, 2021)
This research is motivated by the lack of learning methods applied to the yellow book learning. The purpose of this study is to determine the planning, implementation, and evaluation of the Islamic classic book, known also as Kitab Kuning. The research method used a qualitative research method. The data collection techniques used observation analysis, interview, and documentation study. The results of the research based on direct observation, documentation and interviews with clerics, teaching boards, administrative staff and santri administrators can be summarized as follows: Planning for learning the Islamic classic book at Pondok Asy Syifa is rooted in kiyai's thinking about the Islamic classic book learning levels due to the absence of a clear lesson plan at the Pondok Asy Syifa. Salafiyah are rooted in the abilities of the santris (students) themselves. The teaching and learning process is carried out every day except Thursday and Friday, the learning of the Islamic classic book is carried out by the teacher/ustadz delivering the subject matter using the method of delivering sorogan, bandongan and rote material. Learning evaluation uses formative evaluation, namely an assessment in the form of nadhaman memorization that is carried out before learning takes place and summative evaluation.